Interpreter to test a program written in pseudocode - Huari Evangelista, Felix (2014)
The purpose of this article is to acquaint the student community that begins in troubleshooting programmatically using the program called PSeInt. This is a program that allows to represent algorithms using pseudocode, chart N-S, flowchart, and then make the respective test. The obvious trend is that the student does not need to know any programming language to use this tool.